ATTACHMENT OF WORKING MOTHERS TO CHILD BONDING - Maharani, Wening Pangesthi (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – As a working mother, there is a responsibility for work, and her role in the household is often a pressure for mothers. Parents, especially mothers, are the individuals who should have the most time with children so that children become close to their mothers. Close relationships with the mother have a significant influence on the future development of the child. While working mothers, their time spent on children and family tends to be shorter. This will be pressure on the mother that can trigger stress. The mother's poor psychological state will also affect the poor interaction between mother and child. It will produce adverse effects, including poor emotional regulation, theory of mind, empathy, bonding, and attachment. The purpose of this study was to find out about working mothers and their relationship to bonding and attachment with children. Methods – In this literature review, articles published within the last five years (2019-2023) are used, written in English, are original research, and the research subjects used are humans, namely working mothers who have children aged 0-12 years. Article search using electronic databases in the form of Google Scholar, PubMed, and ScienceDirect. Results – In this literature review, articles published within the last five years (2019-2023) are used, written in English, are original research, and the research subjects used are humans, namely working mothers who have children aged 0-12 years. Article search using electronic databases such as Google Scholar, PubMed, and ScienceDirect. Discuss – Working mothers feel that roles at work and home are all important. Where work will make individuals professional and increase their self-esteem, while her role as a mother at home will meet the needs of her central family, her children; this role is fulfilled by providing physical and emotional comfort and security to her children. Conclusion – Working mothers will increase pressure and stress on mothers caused by many factors, including longer working time, single mothers, lack of financial problems, short maternity leave, and job demands that cause fatigue. These factors will cause poor interaction between mother and child, directly mediating poor bonding and attachment between mother and child. Therefore, balancing the mother's dual roles is essential to form bonds and secure attachments with her child.